Towards a Religion–Victimization Module for the International Self-Report Delinquency Study (ISRD) Context: Learning from Prior Exemplars - Litvak, Sophie; Kivivuori, Janne; Kaakinen, Markus (Kriminologijos studijos, 2023)
The concept of postsecular society highlights the increasing relevance of religion in social, cultural, and political affairs. Given this trend, criminology should pay increasing attention to how religion is linked to victimization and offending. Since the religion–crime studies have traditionally focused on offending, the research lacunae are biggest in the study of victimization. The inclusion of religion is particularly relevant in international surveys in religiously heterogeneous communities. In this article, we aim to develop a survey module suggestion for use in the context of the International Self-Report Delinquency Study (ISRD). We first examine the current content of the ISRD-4 sweep. To locate lacunae in it, we move to review how international surveys have tackled the dimension of religion, including the Health Behaviour in School-aged Children (HBSC) study, the European School Survey Project on Alcohol and Other Drugs (ESPAD), the European Social Survey (ESS), the World Values Survey (WVS), and the International Crime Victim Survey (ICVS). Building on these state-of-the-art examples, we propose a new ISRD module (Appendix) for studying the religion–victimization link in international crime surveys with limited space. In conclusion, we argue that criminology would benefit from increasing attention to religion and other cultural variables alongside traditional socioeconomic, structural, and individual factors.